Pharmacological effects of Chinese medicine modulating NLRP3 inflammasomes in fatty liver treatment - Liu, Tingting; Xu, Guang; Liang, Longxin; Xiao, Xiaohe; Zhao, Yanling; Bai, Zhaofang (Frontiers in Pharmacology, 2022)
Inflammation is a key contributing factor in the pathogenesis of fatty liver diseases (FLD), such as nonalcoholic fatty liver disease (NAFLD), and alcohol-associated liver diseases (ALD). The NLRP3 inflammasome is widely present in the hepatic parenchymal and non-parenchymal cells, which are assembled and activated by sensing intracellular and extracellular danger signals resulting in the matures of IL-1β/ IL-18 and pyroptosis. Moreover, the aberrant activation of NLRP3 inflammasome is considered the main factor to drive immune outbreaks in relation to hepatic injury, inflammation, steatosis, and fibrosis. Therefore, inhibition of NLRP3 inflammasome may be a promising therapeutic target for FLD. Currently, accumulating evidence has revealed a number of traditional Chinese medicine exert beneficial effects on liver injury via inhibiting NLRP3 inflammasome activation. Here, we summarized the mechanism of the NLRP3 inflammasome in the initiation and progression of FLD, and TCM exerts beneficial effects on FLD via positive modulation of inflammation. We describe that TCM is a promising valuable resource for the prevention and treatment agents against FLD, and has the potential to be developed into clinical drugs.